Analisis kestabilan Terowongan SOD level 7 pada tambang bijih emas bawah tanah Di PT. Dempo maju cemerlang pesisir selatan - Halid candra; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Dempo maju Cemerlang is a company operating in the gold mining sector. Gold mining of PT. Dempo maju cemerlang using an underground mining system with the skrinkage method. Mining is carried out by tunneling the main entrance and access to the ore deposits . So that tunnel enlargement activities are carried out to facilitate access to the location and transportation of mining products. So that the tunnel causes a decrease in the safety factor from 3,576 to 1,772 so it is necessary to install a buffer system. The support system must be carefully determined so that its use is optimal , at the SOD level 7 location, the depth of 500- 510 meters has not been used. So that the installation of a buffer will be carried outsplit setaccording to the total collapse load obtained from the tunnel. Analysis needs to be done to determine the condition and rock mass class and to determine the proper installation of supports to the tunnel. The RMR value ranges from 49 - 59, which means the rock mass is categorized into class III rock (f air rock). The support for the split set that must be installed in the tunnel is 3 split sets per meter so that the security factor of the tunnel is stable, meaning it is in accordance with the expected safety factor. Keywords: Tunnel, Safety Factor, RMR-System, Ground Suppor